Heterogeneous interface anti-cracking method based on multi-element dot matrix compounding
By constructing a high-strength three-dimensional mesh dot matrix and high toughness phase filling at the heterogeneous metal interface, the problem of prone to cracking of the heterogeneous metal interface is solved, and the reliability and life of the heterogeneous structure are achieved.
Patent Information
- Application Number
- CN202510652345.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-21
- Publication Date
- 2025-08-05
- Estimated Expiration
- 2045-05-21
AI Technical Summary
The prior art is difficult to effectively strengthen the heterogeneous metal interface, especially in heterostructures with large differences in thermal expansion properties, interface cracking is prone to occur during additive manufacturing, limiting its engineering application.
Multiple lattice composite method is used to construct a high-strength three-dimensional mesh dot matrix at the interface of heterogeneous materials, and cooperate with high toughness phase filling. Through the steps of selective laser melting and manufacturing, low-temperature diffusion strengthening in the phase interface, a coordinated structure between the hard phase and soft phase is formed, which enhances the interface binding strength and crack-blocking ability.
It improves the crack resistance and structural integrity of heterogeneous interfaces, and is suitable for a variety of heterogeneous material systems, extends component life and improves comprehensive performance.
Smart Images

Figure CN120421531A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of additive manufacturing and relates to a heterogeneous interface anti-cracking method based on multi-element lattice composite. Background Art
[0002] Heterogeneous structural materials, also known as gradient composite materials, are a new class of materials with excellent comprehensive mechanical properties. They are typically composed of two or more materials distributed according to the specific performance requirements of each component. They offer advantages such as a wide design domain, performance gradients, and highly designable material layouts. Compared to aircraft airframe components made of homogeneous materials, heterogeneous structural materials can integrate multiple properties, including heat protection, high-temperature resistance, corrosion resistance, high strength, and high toughness. This effectively improves the structural efficiency of aircraft airframes and becomes a key entry point for innovative breakthroughs in aircraft airframe structures. Additive manufacturing holds broad prospects for the design, manufacturing, and application of heterogeneous structures. NASA and other organizations have demonstrated the application of full-scale HR-1 / Cu bimetallic heterogeneous rocket engine combustion chambers and TC4 / TiAl engine compressor impellers. NASA has also successfully printed and ground-tested high-temperature alloy-copper alloy heterogeneous rocket engine combustion chambers. Similarly, the Marshall Center designed and additively manufactured a rotating detonation rocket engine using a GRCop 42 / Monel K500 heterogeneous metal system. During ground testing, the gradient-structured engine generated a sustained and stable thrust of 28,000 N for 251 seconds. While additively manufactured heterogeneous metal components have achieved component-level application verification abroad, current research in China on heterogeneous additive manufacturing remains at the laboratory test block / test piece level, lacking systematic and comprehensive verification and evaluation methods. Consequently, progress in engineering applications has been slow.
[0003] The main reason for this is that the interface performance of the current heterogeneous structure is weak and difficult to meet service requirements. When additively manufacturing heterogeneous metals, the cross-diffusion of multiple elements in the transition layer of the heterogeneous material leads to complex interface reactions, which easily form brittle precipitation phases and deteriorate the mechanical properties of the interface. What is more serious is that the network structure formed by the enrichment of the brittle phase will further induce interlayer embrittlement and cracking. In addition, affected by the sudden heating and cooling characteristics of high-energy beam additive manufacturing, the solid-state phase change behavior of each deposited layer is different. In addition, the thermal expansion properties of heterogeneous materials are different, making it difficult to fully release the concentrated thermal stress in the heterogeneous structure additive process, inducing cracking and failure in the weak interface area. Therefore, in order to promote the engineering application of heterogeneous gradient materials / structures, it is urgent to develop matching interface strengthening technologies.
[0004] A review of existing research on heterogeneous interface strengthening reveals that the main approaches include adding transition layers, interface topology, and interfacial structural meshing. The goal of using transition layers for interlayer interface strengthening is to facilitate a smooth transition in properties between multiple metal materials while preventing cross-diffusion of the metals on either side to form brittle and harmful phases. Currently, transition layer interface strengthening technology is primarily applied to homogeneous metals or heterogeneous systems with limited harmful phases, such as high-strength titanium alloys and medium-strength titanium alloys, or refractory zirconium and high-thermal-conductivity copper alloys. Interface topology primarily focuses on lightweighting, considering the stiffness and strength constraints of heterogeneous structures at high temperatures and additive manufacturing process constraints. Interface topology is designed to strengthen the interface by designing the topology of the dissimilar material interface. Currently, interface topology is primarily used between different titanium alloys or in heterogeneous systems without intermetallic compounds. When employing interfacial structural meshing, specific characteristic structures, such as tooth-shaped, staggered, and wedge-shaped, are typically arranged at the heterogeneous interface, either at a single scale or multiple scales, to strengthen the interface. Testing has shown that interfacial structural meshing can strengthen the interface, with the overall mechanical properties showing significant improvements compared to conventional flat interfaces.
[0005] However, most of the above heterogeneous interface strengthening methods are only suitable for heterogeneous metal systems with relatively similar physical and chemical properties, such as titanium alloy-titanium alloy, titanium alloy-titanium-based composites, stainless steel-copper alloy, etc. Conventional methods are often difficult to apply to systems with large differences in thermal expansion properties (high-temperature alloy-titanium alloy, heat-resistant ceramic-titanium alloy, etc.). Interface cracking caused by thermal stress concentration is still the main factor limiting the application of this type of heterogeneous structure. When using composition transition / barrier layer transition for interface strengthening, the interface still forms a brittle harmful phase enrichment area within a hundred microns on both sides of the bonding area. Moreover, the transition layer only strengthens the interface at the composition level. Adding a transition layer at the structural level is not conducive to the overall mechanical properties of the component. When adopting interface topology and special-shaped structure meshing, the strengthening effect is relatively limited. Under the conditions of sudden heating and cooling of additive manufacturing, it is impossible to fully strengthen the heterogeneous material system with large differences in physical and chemical properties. Therefore, the existing methods cannot fundamentally strengthen the interlayer interface of heterogeneous metals. Summary of the Invention
[0006] In response to the problems existing in the prior art, the present invention provides a heterogeneous interface anti-cracking method based on multi-element lattice composite. The target object is the heterogeneous interlayer interface of gradient composite and layered material. The corresponding improvement of anti-cracking performance is achieved based on the synergistic effect of the high-strength three-dimensional network lattice and high-toughness filling phase of the heterogeneous interface. The orderly distributed hard skeleton and soft phase give the heterogeneous interface sufficient bonding strength and the ability to prevent crack propagation. It has the advantages of high reliability, strong universality, and obvious advantages of structural life extension. The specific implementation method is to construct a high-strength three-dimensional mesh lattice at the interface of heterogeneous materials to strengthen the interface bonding strength, and fill the lattice gap with a high-toughness reinforcement phase with plastic deformation ability to release the interface stress, thereby achieving the effect of blocking the expansion of heterogeneous interface cracks and ensuring the integrity of the interface structure. The specific process is: three-dimensional mesh lattice configuration design-selective laser melting manufacturing-medium-temperature infiltration filling of high-toughness phase-medium-low temperature diffusion strengthening of phase interface-heterogeneous structure composite forming. An orderly distributed hard skeleton and soft filling phase are constructed at the interface of heterogeneous materials. The continuously distributed hard phase forms a three-dimensional mesh lattice, which provides sufficient bonding strength for the heterogeneous material interface. The soft phase is filled in it to provide a certain plastic deformation ability for the interface to block the expansion of interface cracks. Based on the synergistic effect of the multi-hard lattice and the soft phase, the concentrated thermal stress in the process of heterogeneous material additive manufacturing is released, the interface crack resistance is improved, and the structural integrity is guaranteed. The interface strengthening of the present invention is achieved through a series of steps including three-dimensional lattice configuration design - selective laser melting manufacturing - medium-temperature infiltration filling of high-toughness phase - medium-low temperature diffusion strengthening of phase interface - heterogeneous structure composite forming.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for resisting cracking of heterogeneous interfaces based on multi-element lattice composites, wherein the multi-element lattice composites specifically refer to continuously distributed hard phases and soft filling phases, which are collaboratively constructed into a three-dimensional network structure at the heterogeneous interface. The hard skeleton and the soft phase respectively give the heterogeneous interface sufficient bonding strength and the ability to block crack propagation. The specific implementation process of the multi-element lattice composite is mainly divided into two parts: the design and manufacture of the hard three-dimensional network lattice and the filling of the gap by the soft phase. The present invention relates to a specific implementation process of the heterogeneous interface of the multi-element lattice composite, which is the design of the three-dimensional network lattice configuration, selective laser melting manufacturing, medium-temperature infiltration and filling of the high-toughness phase, medium-low temperature diffusion strengthening of the phase interface, and heterogeneous structure composite forming. Specifically comprising the following steps:
[0009] Step 1: Design of three-dimensional mesh lattice configuration. A and B represent the two materials contained in the heterogeneous layered structure, and X1 and X2 represent the hard phase and soft phase at the interface. Compare and analyze the crystal structure, thermal conductivity, thermal expansion coefficient, strong plasticity and other property parameters of materials A and B, and comprehensively consider multiple factors to qualitatively evaluate the degree of difference in the properties of the two types of materials. Based on the degree of difference in properties, select the hard phase X1 and design the lattice structure to ensure that it can provide sufficient support and strength during actual service, while ensuring that it can fully form a stable phase interface with the subsequent soft phase parts.
[0010] Step 2: Selective Laser Melting. After the lattice configuration is designed, the three-dimensional lattice is fabricated using selective laser melting technology. A high-energy beam melts the powder material layer by layer, gradually building the designed three-dimensional network structure.
[0011] Step 3: Medium-temperature infiltration of the high-toughness phase. Based on the degree of disparity in the properties of the heterogeneous materials determined in Step 1, the type of soft phase X2 material to fill the interface is selected, with a focus on the material's toughness and plastic deformation capacity. Once the soft phase is identified, the soft phase block is placed above the hard lattice. Both are heated to a specific temperature—above the melting point of the soft phase but below the softening temperature of the hard phase—to ensure that the molten soft phase penetrates and fully fills the lattice gaps, forming a tightly bonded interface.
[0012] Step 4: Diffusion strengthening at medium and low temperatures at the interface. After the soft phase is filled, the entire structure is placed at medium and low temperatures for atomic diffusion at the interface between the hard skeleton and the soft phase. This forms an elemental interdiffusion layer near the interface, further strengthening the interlayer interface bonding strength and improving the heterogeneous interface's resistance to crack growth.
[0013] Step 5: Heterogeneous structure composite forming. Based on the multi-element lattice layer X1-X2 / A material structure completed in the above steps, the B material is manufactured on the surface of the multi-element lattice layer using additive manufacturing and other technologies to obtain the A / X1-X2 / B heterogeneous layered structure.
[0014] Furthermore, the heterogeneous interface anti-cracking method is suitable for interface strengthening between homogeneous alloys, such as titanium alloys (TA15, TC4, TC11, Ti65), copper alloys (CuCrZr, CuAg), etc., and is also suitable for heterogeneous systems with large differences in physical and chemical properties or the presence of intermetallic compounds, such as heat-resistant ceramics and metals, high-temperature alloys and titanium alloys, and high-temperature alloys and titanium-based composite materials.
[0015] Furthermore, in the material selection of the hard phase X1, priority is given to using materials that are lightweight, high-strength, and have a certain plastic deformation capability. The main selection principle is to ensure sufficient bonding strength of the heterogeneous interface.
[0016] Furthermore, the design of the three-dimensional mesh lattice configuration evaluates the degree of difference in the properties of materials A and B, primarily referring to key properties that determine the mechanical properties of the interface, including crystal structure a1, thermal conductivity a2, and thermal expansion coefficient a3. This criterion is based on the interface mechanical properties evaluation model q(a) = f(a1, a2, a3…). By presetting representative values for each performance parameter, the q value for each material is calculated. The q values of the target materials A and B are then compared to guide the mesh lattice design.
[0017] Furthermore, the interface three-dimensional mesh lattice design method based on the material q value is specifically as follows: 1) when qA / qB of the two types of materials is greater than 10, it indicates that the physical and chemical properties of A and B are quite different, and a double-sided dense + central dense mesh lattice structure is adopted; 2) when qA / qB is between 1 and 10, it indicates that the physical and chemical properties of A and B are moderately different, and an overall dense mesh lattice structure is adopted; 3) when qA / qB is less than 1, the physical and chemical properties of the two materials are relatively small, and a moderate density mesh lattice structure is adopted.
[0018] Furthermore, the differences between the three types of grid structures—dense, compact, and moderately dense—are in the size of the individual cells. The smaller the individual cell size, the denser the three-dimensional grid lattice formed within the heterogeneous material transition zone, and the greater the performance gain in interface bonding strength. The unit cell size of a dense grid is 1 to 3 mm, the unit cell size of a compact grid is 3 to 6 mm, and the unit cell size of a moderately dense grid is 6 to 10 mm.
[0019] Furthermore, in the laser selective melting manufacturing of the three-dimensional lattice of the interface, the laser scanning rate should be appropriately increased during the parameter setting process to promote the roughening of the surface of the hard phase lattice forming, so as to increase the surface area of the lattice and enhance the subsequent interface bonding with the soft phase.
[0020] Furthermore, the selection of the soft phase in step three also refers to the qA / qB value given by the interface mechanical properties evaluation model, specifically: 1) when qA / qB is greater than 10, a material with high toughness and strong plastic deformation ability is selected; 2) when qA / qB is between 1 and 10, a material with moderate plasticity and toughness is selected; 3) when qA / qB is less than 1, a material with relatively good plasticity and toughness is selected.
[0021] Furthermore, the infiltration filling of the soft phase in step three needs to be controlled in a specific temperature environment. Usually, the ambient temperature needs to be higher than the melting point of the soft phase and lower than the softening temperature of the hard phase. It is usually appropriate to take 100-200°C at the softening temperature of the hard phase. The overall infiltration time is determined according to the system. The specific criterion is that the soft phase has basically filled the hard three-dimensional lattice under visual conditions.
[0022] Furthermore, the diffusion strengthening of the hard and soft phases at low and medium temperatures in step 4 aims to further strengthen the interface. This low and medium temperature environment corresponds to 300-500°C below the melting point of the soft phase, and should be maintained for at least 3 hours to allow for sufficient cross-diffusion of elements at the interface, enhancing interfacial bonding strength and crack growth resistance.
[0023] Furthermore, the additive forming of material B on the surface of the multi-component composite lattice structure in step five can be completed by various methods such as laser cladding, laser selective melting, and laser fuse additive manufacturing. Within the initial 10 layers of material B, 60% to 80% of the heat input of the normal process parameters should be used to ensure the integrity of the multi-component composite lattice structure.
[0024] Compared with the existing heterostructure interface control technology, the present invention has the following beneficial effects:
[0025] 1) The hard and soft phases work synergistically, resulting in high reliability. The dense three-dimensional lattice structure formed by the hard phase effectively increases the interfacial bonding strength of the heterostructure. The soft phase, filling the interstitial gaps, enhances the interface's plastic toughness and crack propagation resistance, hindering crack initiation and propagation through its own moderate deformation. The two phases work together efficiently, enhancing the reliability of the heterostructure.
[0026] 2) Designing interface structures based on material property differences is highly universal. By focusing on the material property difference criteria of the interface mechanical performance evaluation model, the selection of hard and soft phases and the design of specific multi-component composite lattice structures are completed. This approach is applicable to both homogeneous alloys with similar properties and systems with significantly different properties, such as heat-resistant ceramic-metal and high-temperature alloy-titanium alloy.
[0027] 3) Multi-element lattice composites inhibit crack propagation, extending the life of the structure. Relying on the composite multi-element lattice of the heterogeneous interface and the gradual change of the longitudinal structure of the lattice, when a crack appears at the interface, the stress is released by the deformation of the soft phase, and the crack propagation is blocked when it reaches the phase interface. This controls the extension of harmful cracks to a single or a few cells, extending the life of the component structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the implementation process of heterogeneous interface anti-cracking technology based on multi-element lattice composite;
[0029] Figure 2 It is a diagram of various types of three-dimensional lattice configuration structures;
[0030] Figure 3 The diagram shows the mechanism of preventing crack propagation of multi-element lattice composite reinforced heterogeneous interface after service in thermal environment;
[0031] Figure 4 Metallographic photographs of gradient structure cross sections at different magnifications showing only composition transition;
[0032] In the figure: 1 high-energy beam, 2 hard three-dimensional network structure, 3 soft filling phase, 4 sealed protective atmosphere heating equipment, 5 interface element interactive diffusion layer, 6B material, 7 double-sided dense mesh lattice, 8 central dense grid lattice structure, 9 moderate density grid lattice, 10 hexagonal grid lattice, 11 local microcracks. DETAILED DESCRIPTION
[0033] The present invention is further described below with reference to specific implementation cases.
[0034] Figure 1 This is a schematic diagram of the implementation process of heterogeneous interface anti-cracking technology based on multi-element lattice composite. Figure 2 It is a diagram of various types of three-dimensional lattice configuration structures. Figure 3 This is a diagram showing the mechanism of preventing crack propagation of the multi-element lattice composite reinforced heterogeneous interface after service in a thermal environment. Figure 4 This is a metallographic photograph of a gradient structure cross section with only composition transition.
[0035] The present invention uses a multi-element lattice composite method to enhance the crack resistance of heterogeneous material interfaces. The method uses a hard phase and a soft phase to decouple the heterogeneous interface's requirements for bonding strength and plastic deformation / crack propagation retardation. Specifically, the hard phase forms a dense three-dimensional lattice structure to enhance interface bonding strength, while the soft phase fills the lattice gaps to enhance interface plastic toughness and inhibit the initiation and propagation of crack defects. The proposed multi-element lattice composite anti-cracking technology is applicable to both homogeneous metals and heterogeneous systems with significantly different physical and chemical properties. It mainly includes the following steps: three-dimensional lattice configuration design - selective laser melting manufacturing - medium-temperature infiltration filling of the high-toughness phase - medium-low temperature diffusion strengthening of the phase interface - and heterogeneous structure composite forming.
[0036] Three-dimensional mesh lattice configuration design. Figure 1 As shown in Figure a, A and B represent the two materials comprising the heterogeneous layered structure, and X1 and X2 represent the hard and soft phases at the interface. When selecting materials for the hard phase X1, priority is given to lightweight, high-strength materials with a certain degree of plastic deformation, such as niobium alloys. When designing the three-dimensional lattice configuration, the crystal structure a1, thermal conductivity a2, and thermal expansion coefficient a3 of materials A and B are input. The values of qA, qB, and qA / qB are calculated based on the interface mechanical properties evaluation model q(a) = f(a1, a2, a3…). When qA / qB is greater than 10, a double-sided dense + central dense lattice structure is adopted; when qA / qB is between 1 and 10, an overall dense lattice structure is adopted; and when qA / qB is less than 1, a moderately dense lattice structure is adopted. The unit cell size of each type of grid gradually decreases according to dense, compact, and moderate density. The unit cell size of dense grid is 1 to 3 mm, the unit cell size of compact grid is 3 to 6 mm, and the unit cell size of moderate density grid is 6 to 10 mm.
[0037] Selective laser melting manufacturing. After completing the lattice configuration design, the selective laser melting forming technology is used to manufacture the three-dimensional lattice, such as Figure 1 As shown in Figure b, a high-energy beam 1 melts the powder material layer by layer, gradually building a designed three-dimensional network structure 2. During parameter setting, the laser scanning rate is increased by 10-20% compared to conventional parameters, allowing the laser beam to scan rapidly across the forming area. This promotes the roughening of the formed surface of the hard phase lattice, increasing the lattice's surface area and enhancing subsequent interfacial bonding with the soft phase.
[0038] The high-toughness phase is filled by medium-temperature infiltration. The selection of soft phase 3 also refers to the qA / qB value given by the interface mechanical properties evaluation model. When qA / qB is greater than 10, materials with high toughness and strong plastic deformation ability are used; when qA / qB is between 1 and 10, materials with moderate plasticity and toughness are used; when qA / qB is less than 1, materials with relatively good plasticity and toughness are used. After determining the soft phase, the soft phase block is placed above the hard lattice, such as Figure 1 As shown in c, it is appropriate to heat both to 100-200°C, the softening temperature of the hard phase. When the soft phase has basically filled the hard three-dimensional lattice visually, it is determined that the high-toughness phase is filled.
[0039] After the soft phase is filled, the whole structure is placed in a sealed protective atmosphere heating device 4, such as Figure 1 As shown in Figure d, the temperature is set to 300-500°C below the melting point of the soft phase, and the time should be no less than 3 hours to carry out atomic diffusion at the interface between the hard skeleton and the soft phase, so that an element interdiffusion layer 5 is formed near the interface, further strengthening the interlayer interface bonding strength and improving the heterogeneous interface's ability to resist crack growth.
[0040] Heterogeneous structure composite forming. Based on the multi-element lattice layer X1-X2 / A material structure completed in the above steps, the additive forming technology is used to complete the manufacturing of B material 6 on the surface of the multi-element lattice layer, such as Figure 1 As shown in Figure e, a heterogeneous layered structure A / X1-X2 / B is obtained. Fabrication of material B can be accomplished through various methods, including laser cladding, selective laser melting, and laser fuse additive manufacturing. During the initial formation of the 10 layers of material B, a heat input of 60–80% of the normal process parameters should be used to ensure the integrity of the multi-component composite lattice structure.
[0041] The three-dimensional network lattice composed of the hard phase, its grid shape, density and other characteristics are mainly determined by the qA / qB value calculated by the interface mechanical properties evaluation model, such as Figure 2 As shown, when qA / qB is greater than 10, a double-sided dense 7+ center dense 8 grid lattice structure is adopted ( Figure 2 a); When qA / qB is between 1 and 10, the overall dense grid lattice structure is adopted ( Figure 2 b); When qA / qB is less than 1, a grid lattice structure with moderate density is adopted, such as Figure 2 At the same time, the grid shape can also be designed as a hexagon 10 according to the service performance requirements to accommodate more soft filling phases to enhance the interface crack resistance and inhibit crack propagation capabilities.
[0042] Based on the heterogeneous metal structure after multi-element lattice composite strengthening ( Figure 3 a) After serving in an extreme force-heat coupling environment for a period of time, the heterogeneous interface will inevitably form concentrated thermal stress under the influence of the thermal expansion properties of the materials on both sides, resulting in overall structural deformation and interface cracking, such as Figure 3 As shown in Figure 2b, a localized microcrack 11 initiates and propagates in all directions. At this point, the hard phase lattice structure ensures the bonding strength of the heterogeneous interface, while the soft phase's inherent plastic deformation capacity hinders crack propagation. Through the synergistic effect of the hard and soft phases, crack propagation is suppressed within a specific hard lattice, thereby enhancing the heterogeneous metal structure's crack propagation resistance and extending its service life.
[0043] In this embodiment, GH4169 high-temperature alloy and Ti6Al4V titanium alloy are selected to form a heterogeneous alloy, and the forming and manufacturing sequence is high-temperature alloy-multi-component composite lattice-titanium alloy. When manufacturing high-temperature alloys and titanium alloys, laser melting deposition is used as the manufacturing method. When manufacturing cemented carbide three-dimensional lattices, selective laser melting forming technology is adopted, and high-strength titanium alloy is used as the hard lattice material. Comprehensively considering the crystal structure, thermal conductivity, and thermal expansion coefficient of high-temperature alloy A and titanium alloy B, based on the interface mechanical properties evaluation model q(a)=f(a1,a2,a3…), qA / qB is calculated to be 16.4, so a double-sided dense + central dense grid lattice structure is adopted. The unit cell size of the central dense grid is 2mm, and the unit cell size of the two-sided dense grid is 5mm.
[0044] The material selection for filling the soft phase was based on the qA / qB value (16.4) of a high-temperature alloy-titanium alloy heterostructure. A material with high toughness and strong plastic deformation capability was selected. In this example, metallic copper was chosen as the soft phase. A copper block was placed atop a hard lattice and both heated to 1500°C. The high-toughness phase was considered complete when the copper had essentially filled the hard three-dimensional lattice.
[0045] The entire structure was then heated to 600°C, below the melting point of the soft phase, for 4 hours to allow atomic diffusion at the interface between the hard skeleton and the soft phase. Additive manufacturing of Ti6Al4V was then performed on the multi-component composite lattice surface, resulting in a GH4169-Ti6Al4V layered composite structure.
[0046] Comparative Example 1
[0047] The heterogeneous system in this comparative example is composed of GH4169 high-temperature alloy and Ti6Al4V titanium alloy, and is also formed and manufactured using laser melting deposition technology. Unlike the embodiment, this example only uses metallic copper as the intermediate layer of the heterogeneous structure and does not adopt the multi-element lattice composite interface crack resistance technology.
[0048] The manufacturing process of the GH4169-Cu-Ti6Al4V heterostructure involved in the comparative example is mainly divided into the following steps: selective laser melting forming of GH4169, laser melting deposition of Cu intermediate layer, laser melting deposition of Ti6Al4V, and heat treatment and machining of the overall heterostructure.
[0049] For the obtained heterostructure, the interface structure of the heterostructure is characterized, such as Figure 4 As shown, the heterojunction interface is densely populated with microcracks extending from the transition zone to both sides. These cracks extend horizontally through the heterojunction interface, sometimes even extending into the interior of the GH4169, forming cross-interface cracks and causing surface spalling. The appearance of interfacial cracks demonstrates that strengthening the heterojunction interface based solely on compositional transitions is ineffective.
[0050] The above-described embodiments merely express the implementation methods of the present invention, but should not be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all fall within the scope of protection of the present invention.
Claims
1. A heterogeneous interface anti-cracking method based on multi-element lattice composite, characterized in that: The multi-element lattice composite specifically refers to a continuously distributed hard phase and a soft filling phase, which are synergistically constructed into a three-dimensional network structure at the heterogeneous interface. The hard skeleton and the soft phase respectively give the heterogeneous interface sufficient bonding strength and the ability to block crack propagation. The specific implementation process of the multi-element lattice composite is the design of the three-dimensional network lattice configuration, the selective laser melting manufacturing, the medium-temperature infiltration filling of the high-toughness phase, the medium-low temperature diffusion strengthening of the phase interface, and the heterogeneous structure composite forming. The specific steps include: Step 1: Three-dimensional mesh lattice configuration design; A and B represent the two materials contained in the heterogeneous layered structure, and X1 and X2 represent the hard and soft phases at the interface. The key properties of materials A and B are compared and analyzed, and the degree of property difference between the two types of materials is qualitatively evaluated based on a combination of multiple factors. Based on the degree of property difference, the hard phase X1 is selected and the lattice structure is designed to ensure that it can provide sufficient support and strength during actual service, while ensuring that it can fully form a stable phase interface with the subsequent soft phase component. Step 2: Selective laser melting manufacturing: After completing the lattice configuration design, the three-dimensional lattice is manufactured using selective laser melting technology. The powder material is melted layer by layer with a high-energy beam, gradually building the designed three-dimensional network structure. Step 3: Medium-temperature infiltration and filling of the high-toughness phase. Based on the degree of difference in the properties of the heterogeneous materials determined in Step 1, the type of soft phase X2 material to be filled at the interface is selected, with a focus on the material's toughness and plastic deformation capacity. After the soft phase is determined, the soft phase block is placed on top of the hard lattice. Both are heated to a specific temperature that is higher than the melting point of the soft phase but lower than the softening temperature of the hard phase, ensuring that the molten soft phase penetrates and fully fills the lattice gaps to form a tightly bonded interface. Step 4: Diffusion strengthening at medium and low temperature at the phase interface: After the soft phase is filled, the entire structure is placed at medium and low temperature for atomic diffusion at the interface between the hard skeleton and the soft phase, so that an element cross-diffusion layer is formed near the phase interface, further strengthening the interlayer interface bonding strength and improving the heterogeneous interface's crack growth resistance. Step 5: Heterogeneous structure composite forming: Based on the multi-element lattice layer X1-X2 / A material structure completed in the above steps, the B material is manufactured on the surface of the multi-element lattice layer using additive manufacturing and other technologies to obtain an A / X1-X2 / B heterogeneous layered structure.
2. The method for resisting heterogeneous interface cracking based on multi-element lattice composite according to claim 1, characterized in that: In the step 1, in the design phase of the three-dimensional mesh lattice configuration, the degree of difference in the properties of the two types of materials A and B is evaluated, mainly referring to the key properties that determine the interface mechanical properties, specifically including the crystal structure a1, thermal conductivity a2, thermal expansion coefficient a3, and strong plasticity a4; the main basis for providing the judgment criterion is the interface mechanical property evaluation model q(a)=f(a1, a2, a3...), by presetting the representative values of each performance parameter, calculating the q value of each material, and then comparing the q values of the target system A and B materials to guide the mesh lattice design.
3. The method for resisting heterogeneous interface cracking based on multi-element lattice composite according to claim 2, characterized in that: The interface three-dimensional mesh lattice design method based on the material q value is as follows: 1) When qA / qB of the two types of materials is greater than 10, it means that the physical and chemical properties of A and B are very different, and a double-sided dense + central dense mesh lattice structure is adopted; 2) When qA / qB is between 1 and 10, it means that the physical and chemical properties of A and B are moderate, and an overall dense mesh lattice structure is adopted; 3) When qA / qB is less than 1, the physical and chemical properties of the two materials are slightly different, and a moderate-density mesh lattice structure is adopted.
4. The method for resisting heterogeneous interface cracking based on multi-element lattice composite according to claim 3, characterized in that: The difference between the three types of grid structures, dense, compact and moderately dense, lies in the size of a single cell. The smaller the size of a single cell, the denser the three-dimensional grid lattice formed in the transition zone of the corresponding heterogeneous material, and the stronger the performance of the interface bonding strength gain. The unit cell size of the dense grid is 1 to 3 mm, the unit cell size of the compact grid is 3 to 6 mm, and the unit cell size of the moderately dense grid is 6 to 10 mm.
5. The method for resisting heterogeneous interface cracking based on multi-element lattice composite according to claim 1, characterized in that: In the second step, the laser selective melting of the interface three-dimensional lattice is manufactured. During the parameter setting process, the laser scanning rate should be appropriately increased to promote the roughening of the surface of the hard phase lattice formation, thereby increasing the surface area of the lattice and enhancing the subsequent interface bonding with the soft phase.
6. The method for resisting heterogeneous interface cracking based on multi-element lattice composite according to claim 1, characterized in that: In the step three: The selection of the soft phase also refers to the qA / qB value given by the interface mechanical properties evaluation model, specifically: 1) when qA / qB is greater than 10, use materials with high toughness and strong plastic deformation ability; 2) when qA / qB is between 1 and 10, use materials with moderate plasticity and toughness; 3) when qA / qB is less than 1, use materials with relatively good plasticity and toughness; The infiltration filling of the soft phase is carried out in a specific temperature environment, where the ambient temperature is between higher than the melting point of the soft phase and lower than the softening temperature of the hard phase. The overall infiltration time is determined according to the system, and the specific criterion is that the soft phase has basically filled the hard three-dimensional lattice under visual conditions.
7. The method for resisting heterogeneous interface cracking based on multi-element lattice composite according to claim 6, characterized in that: During the infiltration filling of the soft phase, the softening temperature of the hard phase is 100-200°C.
8. The method for resisting heterogeneous interface cracking based on multi-element lattice composite according to claim 1, characterized in that: The step 4 involves diffusion strengthening of the hard phase and the soft phase at medium and low temperatures. The low temperature environment specifically corresponds to 300-500°C below the melting point of the soft phase, and the time is not less than 3 hours to complete the full mutual diffusion of elements at the phase interface.
9. The method for resisting heterogeneous interface cracking based on multi-element lattice composite according to claim 1, characterized in that: In step five, the additive forming of material B on the surface of the multi-component composite lattice structure is completed by various methods such as laser cladding, laser selective melting, and laser fuse additive manufacturing. Within the initial 10 layers of material B, 60% to 80% of the heat input of the normal process parameters is used to ensure the integrity of the multi-component composite lattice structure.
10. The method for resisting heterogeneous interface cracking based on multi-element lattice composite according to claim 1, characterized in that: The heterogeneous interface anti-cracking method is suitable for interface strengthening between homogeneous alloys, and is also suitable for heterogeneous systems with large differences in physical and chemical properties or the presence of intermetallic compounds.
Citation Information
Patent Citations
Multi-reaction system laser additive manufacturing method for high-toughness titanium-based composite material
CN114769619A
Tungsten copper sweating material structural part and multi-material additive manufacturing method thereof
CN117086328A
Gradient metal additive manufacturing method based on cross-scale collaborative interface strengthening
CN119407198A
Manufacture of lightweight metal matrix composites with controlled structure
US20030133821A1
High Toughness Metallic Glass-Based Composites for Additive Manufacturing
US20180345366A1
Cited By
High-temperature titanium alloy forming method based on stress release structure
CN121535209A